Sustaining improvement of hospital-wide initiative for patient safety and quality: a systematic scoping review - Anne Hogden; Kathy Eljiz; Sarah E J Moon (BMJ Open Quality, 2022)
Background Long-term sustained improvement following implementation of hospital-wide quality and safety initiatives is not easily achieved. Comprehensive theoretical and practical understanding of how gained improvements can be sustained to benefit safe and high-quality care is needed. This review aimed to identify enabling and hindering factors and their contributions to improvement sustainability from hospital-wide change to enhance patient safety and quality.Methods A systematic scoping review method was used. Searched were peer-reviewed published records on PubMed, Scopus, World of Science, CINAHL, Health Business Elite, Health Policy Reference Centre and Cochrane Library and grey literature. Review inclusion criteria included contemporary (2010 and onwards), empirical factors to improvement sustainability evaluated after the active implementation, hospital(s) based in the western Organisation for Economic Co-operation and Development countries. Numerical and thematic analyses were undertaken.Results 17 peer-reviewed papers were reviewed. Improvement and implementation approaches were predominantly adopted to guide change. Less than 6 in 10 (53%) of reviewed papers included a guiding framework/model, none with a demonstrated focus on improvement sustainability. With an evaluation time point of 4.3 years on average, 62 factors to improvement sustainability were identified and emerged into three overarching themes: People, Process and Organisational Environment. These entailed, as subthemes, actors and their roles; planning, execution and maintenance of change; and internal contexts that enabled sustainability. Well-coordinated change delivery, customised local integration and continued change effort were three most critical elements. Mechanisms between identified factors emerged in the forms of Influence and Action towards sustained improvement.Conclusions The findings map contemporary empirical factors and their mechanisms towards change sustainability from a hospital-wide initiative to improve patient safety and quality. The identified factors and mechanisms extend current theoretical and empirical knowledgebases of sustaining improvement particularly with those beyond the active implementation. The provided conceptual framework offers an empirically evidenced and actionable guide to assist sustainable organisational change in hospital settings.